The Role of Social Cognition in Depression and Its Relationship to Early Maladaptive Schemas - Debaleena Ghosh; Susmita Halder (Indian Journal of Psychological Medicine)
Background: Social cognition is the capacity to detect, comprehend, and evaluate environmentally relevant information and serves as a critical skill for effective interpersonal functioning. A significant clinical characteristic of depressive illness is the impairment in social and interpersonal functioning. Given the increasing prevalence of interpersonal difficulties among individuals with depression, it is crucial to get a greater insight into the underlying cognitive mechanisms leading to these social deficits. Alongside, early maladaptive schemas (EMS) also serve as proximal cognitive risk factors for depression. Altered socio-cognitive functioning in individuals with can help to draw a connection between impaired social cognition and EMS. In this context, the present study explores the role of social cognition in individuals with depression in relation to EMS. Methods: In this study, individuals of both genders ( N = 60) were pooled based on the inclusion and exclusion criteria and screened for depression through the Beck Depression Inventory. Emotion Recognition and Theory of Mind (ToM) were assessed using the Reading Mind in the Eyes Test (RMET) and Theory of Mind Assessment Scale (TH.O.M.A.S), respectively. EMS was assessed using the Young Schema Questionnaire-Short Form. Results: Results indicate individuals with depression were found to be impaired in both domains of social cognition-emotion recognition and ToM. Individuals with depression also exhibited a greater number of EMS. A significant association was found between EMS and social cognition in depression. Moreover, few of the EMS emerged as significant predictors for social cognition in depression. Conclusion: Individuals with depression exhibit impairment in “reading” social interactions. Moreover, they exhibit specific EMS that emerges as significant predictors of social cognition. Implications of the study focus on recognizing EMS as a tool for addressing the socio-cognitive impairment in depression.